Integrasi Nilai Syariah dalam Pelayanan Medis: Analisis Persepsi dan Praktik Tenaga Kesehatan - Muhammad, Fauzia; Astiwara, Endy Muhammad; Erlina, Andi (Sanus Medical Journal, 2025)
Based on the Decree of the National Sharia Council–MUI No. 13/DSN-MUI/III/2017, Sharia-compliant medical service standards include recitation of basmallah and hamdallah, maintaining patient modesty, same-gender medical procedures, scheduling elective surgeries outside prayer times, Islamic communication and education, and informed consent for non-halal pharmaceutical products. This study aims to analyze the relationship between medical personnel's perception of Sharia-based medical service standards and their implementation, as well as to identify the most influential factors. The research was conducted at YARSI Hospital Jakarta using a mixed-method explanatory design, collecting quantitative data from 76 medical staff via Likert-scale questionnaires and qualitative data through in-depth interviews with general medical specialists. The results showed that medical personnel had a positive perception of Sharia-compliant medical services, which was also reflected in good implementation. The most dominant factors were a supportive work environment, followed by training and spiritual conviction. A strong positive perception can overcome barriers and challenges, positively impacting implementation quality.   Berdasarkan Keputusan Dewan Syariah Nasional–MUI No.13/DSN-MUI/III/2017, standar pelayanan medis sesuai syariah mencakup pembacaan basmallah dan hamdallah, penjagaan aurat, prosedur medis sesuai gender, penjadwalan operasi tidak terbentur waktu salat, komunikasi edukasi Islami, serta informed consent untuk produk non-halal. Penelitian ini menganalisis hubungan persepsi tenaga medis terhadap standar pelayanan medis syariah dengan implementasinya, serta mengidentifikasi faktor dominan yang memengaruhinya. Dilakukan di RS YARSI Jakarta dengan mixed-method explanatory design, menggunakan kuesioner dari 76 tenaga medis dan wawancara dengan dokter spesialis medik dasar. Hasil menunjukkan persepsi tenaga medis yang baik berpengaruh pada implementasi yang baik. Faktor dominan adalah lingkungan kerja yang mendukung, pelatihan, dan keyakinan spiritual. Persepsi positif mampu mengatasi hambatan, berdampak pada kualitas implementasi yang baik.